Genetic screens reveal mechanisms for the transcriptional regulation of tissue-specific genes in normal cells and tumors. Issue 7 (7th February 2019) - Naciri, Ikrame; Laisné, Marthe; Ferry, Laure; Bourmaud, Morgane; Gupta, Nikhil; Di Carlo, Selene; Huna, Anda; Martin, Nadine; Peduto, Lucie; Bernard, David; Kirsh, Olivier; Defossez, Pierre-Antoine
Abstract: The proper tissue-specific regulation of gene expression is essential for development and homeostasis in metazoans. However, the illegitimate expression of normally tissue-restricted genes—like testis- or placenta-specific genes—is frequently observed in tumors; this promotes transformation, but also allows immunotherapy. Two important questions are: how is the expression of these genes controlled in healthy cells? And how is this altered in cancer? To address these questions, we used an unbiased approach to test the ability of 350 distinct genetic or epigenetic perturbations to induce the illegitimate expression of over 40 tissue-restricted genes in primary human cells. We find that almost all of these genes are remarkably resistant to reactivation by a single alteration in signaling pathways or chromatin regulation. However, a few genes differ and are more readily activated; one is the placenta-expressed gene ADAM12, which promotes invasion. Using cellular systems, an animal model, and bioinformatics, we find that a non-canonical but druggable TGF-β/KAT2A/TAK1 axis controls ADAM12 induction in normal and cancer cells. More broadly, our data show that illegitimate gene expression in cancer is an heterogeneous phenomenon, with a few genes activatable by simple events, and most genes likely requiring a combination of events to become reactivated.